2022
DOI: 10.2174/1871530322666220331154354
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led and Interdisciplinary Secondary Cardiovascular Prevention Programmes: Spanish Cohort of the EUROACTION Project

Abstract: Background: Cardiovascular prevention and rehabilitation programmes (CVPRP) are a preventive tool, which can reverse unhealthy behaviours and improve risk factor management. They have been successfully implemented in a variety of settings in patients with coronary heart disease (CHD). Objective: To evaluate an interdisciplinary and nurse-led cardiovascular prevention and rehabilitation programme in patients with coronary heart disease. Method: Six pairs of hospitals were randomised between intervention (IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To support this statement, the EUROACTION Project which was a nurse-led model of cardiovascular prevention and rehabilitation programmes, and which was adapted in Spain has produced a healthier lifestyle. This model has achieved affordable and sustainable therapeutic goals in cardiovascular disease prevention in everyday clinical practice [ 32 ]. In another study based on the intervention of nurses, a significant number (31.5%) of patients with angina showed that they made changes to their diet, and a significant number of patients (23.3%) increased their daily physical exercises, more precisely walking [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To support this statement, the EUROACTION Project which was a nurse-led model of cardiovascular prevention and rehabilitation programmes, and which was adapted in Spain has produced a healthier lifestyle. This model has achieved affordable and sustainable therapeutic goals in cardiovascular disease prevention in everyday clinical practice [ 32 ]. In another study based on the intervention of nurses, a significant number (31.5%) of patients with angina showed that they made changes to their diet, and a significant number of patients (23.3%) increased their daily physical exercises, more precisely walking [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…They share not only PCI patient's lifestyle but also the majority of the coronary risk factors. Therefore, social support needs to be promoted at the household level (Buigues et al, 2022 ; Visseren et al, 2021 ). Especially family involvement is essential for adhering to lifestyle recommendations (De Bacquer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…They share not only PCI patient's lifestyle but also the majority of the coronary risk factors. Therefore, social support needs to be promoted at the household level (Buigues et al, 2022;Visseren et al, 2021).…”
Section: Social Supportmentioning
confidence: 99%
See 2 more Smart Citations